Comparison of vaginal wall sling and modified vaginal wall sling for stress urinary incontinence - Bezerra, Carlos Alberto; Sadi, Marcus Vinicius (São Paulo Medical Journal, 2000)
CONTEXT: There are several controversies about which is the best form of surgical treatment for stress urinary incontinence in women. The vaginal wall sling in its original and modified form were presented by Raz as new options for treatment of these conditions, but there is a lack of comparative clinical trials using both techniques. OBJECTIVE: To compare the effectiveness of the original and the modified vaginal wall sling. DESIGN: A comparative, prospective, non-randomized clinical trial. SETTING: Public and private health care units (Urology Division, Faculty of Medicine of the ABC Foundation, and Universidade Federal de São Paulo / Escola Paulista de Medicina). PARTICIPANTS: Twenty patients with anatomical and intrinsic sphincter deficiency stress urinary incontinence were surgically treated for evaluating the initial results of the vaginal wall sling, from February 5, 1994, to June 27, 1996. INTERVENTIONS: The patients were divided into two groups. Group A (n = 10) were treated with the original vaginal wall sling. Group B (n = 10) were treated with the modified vaginal wall sling. Both groups were statistically similar according to clinical and urodynamic parameters. MAIN MEASUREMENTS: Cure and complication rates. RESULTS: Follow-up ranged from 19 to 43 months (median = 28) for group A. The overall cure rate was 70%. Fifty per cent of the patients had urinary retention of 7 to 35 days. There were no major complications. Follow-up ranged from 14 to 26 months (median = 18) for Group B. The cure rate was 80%. Two patients had urinary retention of 7 and 55 days. There were no major complications. CONCLUSIONS: The vaginal wall sling is as effective as the modified vaginal wall sling but has a higher rate of urinary retention.